Los rincones de trabajo y el proceso de enseñanza aprendizaje - Navarrete Criollo, Evelyn Marisela (2016)
Early childhood education, primary part for development and obtaining meaningful learning, to provide the proper development of children / as. The purpose of this research was to investigate the Learning Early Education Process to see the impact of work corners of children / as of the second stage of the Center for Early Education "Semillitas" Cesar Francisco Naranjo Rumazo, the main objective is determine the correct use of work corners and development in the teaching-learning process, through surveys and direct observation to avoid possible educational problems. To solve this problem activities which enable teachers enjoy a range of practical activities according to the study corner mostly workshops where teachers will be active participants arises, and will help to provide input on training, experience and creativity of teachers to learn optimize the use of each of the corners and whoever they generate diverse and innovative proposals to stimulate learning and development of children / as, target is met within the framework of Early Childhood Education. After assessing the instruments of research, concluded that teachers had no basis for the use of every corner of work on all the time is not optimized to stimulate learning in these spaces, they have not been renovated or are changed periodically corners so the loss of interest by children / as is demonstrated.